A quantitative three-dimensional in situ study of a short fatigue crack in a magnesium alloy - Marrow, T; Mostafavi, M; Hashimoto, T; Thompson, G (Elsevier, 2014)
A previous four-dimensional in situ study of a short crack in a magnesium alloy King et al. (2011), Elektron 21, used synchrotron X-ray computed micro-tomography to follow its three-dimensional development with progressive fatigue cycling through the microstructure, which had been mapped by diffraction contrast tomography to measure grain shapes and crystal orientations in three dimensions. In the present work, very high-resolution post-test examination of the same sample by Serial Block Face Scanning Electron Microscopy (SBFSEM) provided three-dimensional fractographs to investigate the influence of microstructural features on the measured crack propagation rates. Digital volume correlation, applied to the X-ray computed micro-tomography datasets, measured the three-dimensional crack opening displacements and hence the crack opening modes. The short fatigue crack in magnesium propagated with mixed mode opening. Basal plane fracture is a dominant mechanism; hence, boundaries that disrupt the continuity of the basal plane are proposed to influence the crack propagation rate. © 2014 Elsevier Ltd. All rights reserved.